Early Ecological Intelligence: Strategies for Introducing Environmental and Sustainability Concepts in Early Childhood Education - Desi Tri Anggereni; Muhammad Nabahan Azizy (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
Amidst the global ecological crisis, education for sustainable development in early childhood (ECEfS) is crucial, yet it often lacks a holistic and integrated framework. This article aims to fill this gap by proposing a conceptual model for fostering ecological intelligence from an early age. This research employs an integrative literature review method, systematically analyzing and synthesizing relevant international and national literature. The synthesis results show that an effective approach is organized into three fundamental, interconnected dimensions: (1) ‘Heart’ (building affective connection and empathy for nature), (2) ‘Head’ (developing cognitive understanding and systems thinking), and (3) ‘Hands’ (manifesting in tangible action and pro-environmental habit formation). The discussion concludes that these three dimensions are interdependent and must be implemented synergistically within a supportive pedagogical ecosystem to achieve a truly transformative impact.